Moderasi Beragama dan Relevansinya Dengan Pendidikan Islam Perspektif M. Quraish Shihab - Anis Sulistyarini; Ach Khusnan (Jurnal Pendidikan Agama Islam Miazhar, 2022)
Indonesia is a country that has a rich diversity of cultures, ethnicities, races and languages. This diversity has become an identity for the Indonesian nation which is a great potential for the Indonesian state to have various groups of citizens with different customs, cultures and mindsets as well.So that self-awareness is needed from each individual or group that difference is a gift given by Allah SWT which is used as a place to complement each other.Lately, the understanding of radical Islam has become stronger, which is marked by the many cases of intolerance in the name of religion.Acts of extremism in the name of religion often occur in Indonesia. Incidents of suicide bombings, carrying out anarchist acts against groups that do not agree, destroying places of worship of people who are carrying out worship are forms of action that according to them are forms of fighting or jihad in the way of religion. In fact, this action indirectly caused chaos, unrest and many victims fell.In this study, we wanted to find out about the moderation of religion from the perspective of M. Quraish Shihab and its relevance to Islamic education. Therefore, the right method to use is library research.This research was conducted using primary data sources, namely a book by M.Quraish Shihab entitled